Pembelajaran IPS di SD Negeri Pendem II untuk menumbuhkan kearifan lokal melalui wisata gunung Kemukus - Ayatullah Muhammadin AL Fath; Zuniar Mabruri (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
The purpose of this study was to maximize students' learning understanding in class V at SDN Pendem II through the School Literacy Movement in social studies learning using picture story media. This research was conducted using descriptive qualitative research methods. The researcher made direct observations in the field on social studies teaching and learning activities in class V SD which could support the research results. Data collection techniques are carried out by observation, interviews, and documentation. Observations were made at Pendem II Public Elementary School to find out the application of pictorial story media. Interviews were conducted with class teachers, principals and students. Documentation was carried out to strengthen the results of observations and interviews. The research was conducted at SDN Pendem II in grade 5 students. The results of the research after implementing social studies learning through picture stories, showed a change in students' understanding of local wisdom of cultural heritage in grade 5 students. The findings of this study were the application of picture story media to foster local wisdom cultural heritage to students, and can have a good influence on students' understanding of learning in social studies learning.